PENERAPAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KEMAMPUAN INTERPERSONAL SISWA KELAS V DALAM PEMBELAJARAN IPS DI SDN KAMPUNG BULAK 03 - Faiza Nuril Izzati; Arita Marini; Iva Sarifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to improve the interpersonal skills of fifth-grade students at SDN Kampung Bulak 03 through the implementation of the cooperative learning model type group investigation. This research was a Classroom Action Research (CAR) conducted in two cycles, each consisting of three meetings. The subjects of this study were 17 students from class V-B. The results showed that in Cycle I, 58.82% of students achieved a score of ≥75, which increased to 88.24% in Cycle II, surpassing the predetermined success indicator of 80%. Thus, it can be concluded that the implementation of the group investigation model can enhance students’ interpersonal skills, particularly in the aspects of social sensitivity, self-awareness, and social communication through a structured and participatory group work process.